A New Methodology to Evaluate Adsorption Capacity on Nanomaterials - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Arancibia-Miranda, N; Arancibia-Miranda, N (Kluwer Academic Publishers, 2015)
Nanomaterials preparation has undergone great development in recent years, with important applications. The adsorbent properties of these nanomaterials cannot be always done using batch studies, because the nanometric particle size often hinders its physical separation, and this may affect the conclusions regarding adsorption studies. A new and simple method was developed, based on electrochemical measurements. For the validation process, synthetic alumina was used as adsorbent with copper solutions. The solid/solution ratio was kept constant in both the electrochemical and batch methods, optimizing in each case the adsorption equilibration time. Peak current versus Cu2+ concentration linearity was assessed from voltammograms. The electrochemical adsorption was accomplished utilizing cyclic voltammetry before and after the addition of the adsorbent. The amount of sorbed element was determined from the difference between the amount of Cu2+ added and that present in solution at equilibrium. The Langmuir, Freundlich, and Langmuir–Freundlich models were used to fit the experimental data obtained by both methods. The results of the electrochemical methodology have precision and accuracy statistically comparable to those obtained with the batch method. The electrochemical technique has the advantage of shorter adsorbent/adsorbate equilibration times than batch and do not require physical separation, allowing the adsorption on the imogolite to be established. © 2015, Springer Science+Business Media Dordrecht.